Caricature of Vincent Davis - Weller, J.C. (1931)
Caricature of chemist Vincent Davis created by artist J.C. Weller at the 1931 American Chemical Society National Meeting in Buffalo, New York. Per notations accompanying the caricature, Davis served as Director of Research at the Niagara Electrolytic Iron Company and later worked in the Electrochemical Division at E.I. duPont de Nemours.
Keywords: Davis, Vincent; Chemists; Portraits; American Chemical Society; Caricatures and cartoons